Hospitalized patients with breakthrough COVID-19: Clinical features and poor outcome predictors. (May 2022) - Moreno-Perez, Oscar; Ribes, Isabel; Boix, Vicente; Martinez-García, María Ángeles; Otero-Rodriguez, Silvia; Reus, Sergio; Sánchez-Martínez, Rosario; Ramos, Jose Manuel; Chico-Sánchez, Pablo; Merino, Esperanza; ,
Highlights: Patients hospitalized for COVID-19 during the breakthrough were mostly older people These patients had elevated comorbidity and a high mortality rate Predictors of poor outcomes resemble those reported in unvaccinated patients Partially vaccinated patients were younger and had fewer comorbidities Outcomes did not differ between the completely or partially vaccinated groups Abstract: Objectives: To describe breakthrough COVID-19 infection in patients who needed hospitalization and the factors associated with poor outcomes. Methods: We conducted a retrospective study on patients hospitalized with COVID-19 between December 27, 2020, and October 17, 2021, with either a complete vaccination (CV) scheme (diagnosed 2 weeks after the second dose of the Pfizer/Moderna/AstraZeneca or first dose of the Janssen vaccine was administered) or a partial vaccination (PV) scheme. The main outcomes were all-cause mortality and the need for invasive mechanical ventilation (IMV). The baseline factors associated with the outcomes were analyzed by multiple logistic regression to estimate the odds ratios (odds ratio [OR]; 95% confidence interval [CI]). Results: A total of 145 (101 CV) patients were included. The CV subgroup was mainly composed of older males with high comorbidity (Charlson Index ≥3, 72%; immunosuppression, 20%) and with bilateral pneumonia in 63.4%. Limited therapeutic effort (LTE) was agreed upon for 28% of the patients. In the CV subgroup, endotracheal intubation was required in 10.9% of patients, reaching 15.3% when excluding LTE patients; the global mortality was 22.8%, reaching 41.4% in the subgroup with LTE. Although the patients with PV were younger and had fewer comorbidities, the main outcomes did not differ significantly between the CV and PV groups. The predictors of poor outcomes were age ≥ 65 years, confusion, ferritin > 500 mg/L, extensive lung infiltrates, and a Charlson Index ≥ 3. Conclusions: Patients with CV hospitalized because of breakthrough COVID-19 infection tend to be older persons, with comorbidities, and have a high mortality.